Prevention of Ischaemic Heart Disease - Mahmood, Manzoor; Hoque, Md Harisul; Mahmood, SA; Quayum, Mohammad Abdul; Arzu, Jahanara; Rahman, Kazi Sharmin (University Heart Journal, 2015)
Prevention strategies are based on identification and modulation of cardiovascular risk factors. Targeting high risk individuals is cost-effective. More relevant to the practising clinicians is Identification of those individuals in whom intervention (life style or pharmacological) will prevent cardiovascular events (fatal and non-fatal myocardial infarction) and/or the need for interventional or surgical procedures, extending duration and quality of life (QOL). Modification of reversible risk factors (rather than interventional procedures) has been largely responsible for the decline in age-adjusted cardiovascular mortality. University Heart Journal Vol. 10, No. 1, January 2014; 27-30